THE RELATIONSHIP BETWEEN THE CHARACTERISTICS OF THE CHOICE OF TRANSPORTATION MODES IN THE CITY OF WEST JAKARTA DURING THE COVID-19 PANDEMIC - Reizsky Reynaldy; Ken Martina Kasikoen; Darmawan Listya Cahya; Mega Novetrishka Putri (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
The Covid-19 pandemic that has hit the world in recent years has changed the habit of life of many people, with no exception to the West Jakarta City Administration citizen.. Various citizen activities started to adjust to the current living circumstances. This study was conducted to determine the relationship between the characteristics of mode selection and the usage of types of transportation modes in the Administrative City of West Jakarta during the Covid-19 Pandemic. This research data was obtained through an online-based survey regarding the characteristics of the mode selection of citizens of the West Jakarta Administrative City during the Covid-19 Pandemic. The resulting data is processed using statistical correlation analysis based on the chi-square test. The results of the analysis show that the highest proportion of the use of this type of transportation mode is in the Administrative City of West Jakarta during the Covid-19 pandemic, namely 68.5% are private vehicle users and 31.5% are public transport users. which are gender factors, vehicle ownership, SIM ownership, frequency of daily activities, distance travelled, the distance of public transportation facilities from home, distance of public transportation facilities from the activities place, travel time during a pandemic, waiting time for transportation modes, and travel costs have a relationship with the usage of this type of transportation in West Jakarta Administrative City During the Covid-19 Pandemic